Natural and artificial flavoring agents and food dyes - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Handbook of food bioengineering, 2018)
This book examines the use of natural vs. artificial food dyes and flavors, and discusses the newest production and purification methods, recent trends, and benefits of natural agents. Also describes the production of natural flavoring agents and dyes by plants, microorganisms and animals to produce higher quality, safer and more economical foods.